Nutritional properties and consumer preferences of soy-fortified maize snacks at household level to combat hidden hunger. - CGIAR Research Program on Maize (2021)
Utilizing the available and preferred staple to create diversity in nutrient-dense foods at an affordable cost will enhance the maize value chain and improve the nation’s nutritional status.